Laser-Induced Graphene-Based Gas Sensor with PEDOT:PSS/Gold–Platinum Nanocomposites for Highly Sensitive Detection of Methane - Jiaying Sun; Zhuoru Huang; Xiaojing Zhang; Hangming Xiong; Weijie Yu; Shimeng Mou; Wenwu Zhu; Hao Wan (Chemosensors)
Methane is a common intestinal gas that has been linked to a variety of gastrointestinal disorders. In this study, we prepared a LIG-based electrochemical sensor modified with PEDOT:PSS/Au-Pt nanocomposites for high-sensitivity methane detection. LIG’s high porosity, flexibility, and excellent electrical conductivity are beneficial for electrochemical detection. The PEDOT:PSS film is electrodeposited on the electrode surface to amplify the signal further. The synergistic effect of bimetallic nanocomposites can improve the electrochemical catalytic activity and increase the specific surface area and the advantages of active sites. The experimental results show that the LIG sensor has a wide linear detection range (2–500 ppm), a low detection limit (about 0.36 ppm), high sensitivity, and good repeatability. The sensor is easy to manufacture, is low-cost, operates at room temperature, has high sensitivity, has a low detection limit, and is expected to be used for methane breath detection in the future.